Biogenic synthesized nanoparticles a boon to human health. (2021) - John Stephen, Bjorn; Mohan Sharma, Madan; Jain, Devendra; Singh, Abhijeet
Abstract: Zinc oxide nanoparticles (ZnO NP's) have found their way in multiple industries owing to its vast applicability. Its synthesis process generally leaves toxic by-products which are harmful to the ecosystem. This study highlights a simple eco-friendly mode for the synthesis of ZnO NP's using the leaf extract of Averrhoa bilimbi Linn. Mainly found in Asia, the plant is known to have many ethnobotanicals uses with strong antimicrobial and antioxidant potential. Nanoparticles were characterized by various techniques such as UV–Vis spectroscopy which showed absorption peak at 360 nm and TEM analysis which showed the size of the synthesized nanoparticles to be 30–40 nm in diameter. Additionally, the nanoparticles synthesized were found to exhibit antibacterial activity towards Escherichia coli ( E. coli ) and Staphylococcus aureus ( S. aureus ). The synthesized ZnO NP's also showed strong antioxidant potential as exhibited through DPPH assay in a dose dependent manner.